Early markers of the renal complications of insulin dependent diabetes mellitus. Issue 7 (July 1989) - Gibb, D M; Dunger, D; Levin, M; Shah, V; Smith, C; Barratt, T M
Abstract : We investigated the associations between albuminuria, metabolic control, glomerular filtration, blood pressure, and platelet function in children with insulin dependent diabetes mellitus. The geometric mean (95% tolerance levels) albumin excretion (expressed as the geometric mean albumin to creatinine ratio on two overnight urine collections (UA/UC], in 60 diabetic children was 0.72 (0.80-6.9) mg/mmol, significantly greater than in 45 normal children (geometric mean 0.41 (0.14-1.17]. Mean (SD) glomerular filtration rate, measured by 51Cr edetic acid clearance during constant infusion, was significantly greater in diabetic children (129 (20) ml/min/1.73 m2) compared with normal controls (109 (13]. Mean (SD) renal length for height standard deviation score was +0.25 (1.1); systolic blood pressure standard deviation score was 0.15 (0.65), and diastolic blood pressure was 0.51 (0.82). Spontaneous platelet aggregation, expressed as percentage fall in platelet count in stirred whole blood after 2 minutes was 17.8 (9.2)% in the diabetic compared with 12.3 (7.9)% in normal children. UA/UC correlated with renal length and of the children with UA/UC above the normal range, 70% also had a glomerular filtration rate above the normal range. There was a weak correlation between UA/UC and glycated haemoglobin (HbA1c). All children with spontaneous platelet aggregation above normal had had diabetes for more than seven years. These cross sectional data define some of the early markers and inter-relationships that may be important in the development of nephropathy.